Fifteen years of accounting professional's competencies supply and demand: Evidencing actors, competency assessment strategies, and "top three" competencies - Nanja Kroon; Maria do Céu Alves (Administrative Sciences, 2023)
This paper reviews accounting education literature with a focus on the supply of and demand for accounting professional's competencies. Its main objective is to determine which actors are involved in the relationship, ascertain both sides' perspectives, and evidence competency supply and demand over the last 15 years. After a solid selection, the analysis includes 122 empirical articles from 2006 to 2021. The actors and competencies addressed in the relevant literature were identified and strategies used in their assessment were discovered. The identified competencies were then categorized and framed in the five constructs presented by Kroon and Alves. This approach evidenced that mismatches remain between competency expectations and competency supply in the accounting profession. Investigators may consider the results to improve the consistency of research in this field of study, contributing to a theory that is still lacking. Using the identified concepts and the constructs' components, empirical studies can bring substantial practical implications to reduce or eliminate existing competency gaps. This study provides an integrated understanding of the literature on the fit between higher education institutions and the labor market of the accounting professional's competencies. The framing of actors, strategies, and competencies will assist other researchers in augmenting knowledge in this area.
Keywords: 350; accounting professional; competencies; demand; skills; supply; supply-demand convergence; systematic literature review